Association of Circulating Heme Oxygenase-1, Lipid Profile and Coronary Disease Phenotype in Patients with Chronic Coronary Syndrome - Chiara Caselli; Raffaele De Caterina; Rosetta Ragusa; Riccardo Liga; Alessia Gimelli; Arthur J. H. A. Scholte; Aldo Clerico; Juhani Knuuti; Danilo Neglia (MDPI AG, 2021)
Background. The NF-E2-related factor 2 (Nrf2)/Heme Oxygenase-1 (HO-1) pathway has an emerging role in atherosclerosis. Activated by oxidative stress, it is deemed to exert athero-protective effects. We aimed at evaluating the relationships between plasma HO-1, clinical/molecular profiles and coronary disease patterns in patients with chronic coronary syndromes (CCS). Methods. HO-1 was measured in 526 patients (60 ± 9 years, 318 males) with CCS. Coronary computed tomography angiography (CTA) and stress imaging were used to assess the disease phenotype (coronary atherosclerosis and myocardial ischemia) in a subgroup of 347 patients. Results. In the overall population, HO-1 median value (25-75 percentile) was 5.195 (1.75-8.25) ng/mL. Patients with higher HO-1 were more frequently male, had a higher BMI and lower LVEF%, but otherwise similar risk factors than the other patients. Their bio-humoral profile was characterized by higher markers of endothelial/myocardial dysfunction, but lower levels of cholesterol lipoproteins. Coronary artery disease was characterized by more diffuse atherosclerosis, with mainly non-obstructive and calcified plaques, and a higher prevalence of functional ischemia. Conclusion: In patients with CCS, higher plasma HO-1 levels are associated with lower cholesterol and a more diffuse but mainly non-obstructive coronary atherosclerosis, confirming a potential role for the Nrf2/HO-1 pathway as a protective feedback.